2006
DOI: 10.1017/s0031182006001193
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cardiopulmonary function and cardiac muscarinic and adrenergic receptor density adaptation in C57BL/6 mice with chronic Trypanosoma cruzi infection

Abstract: Circulating antibodies in chagasic patients interact with myocardial beta adrenergic and muscarinic cholinergic receptors, triggering intracellular signals that alter cardiac function along the course of the disease. However, until now, experimental data in models of chronically infected chagasic mice linking the effects on myocardial beta adrenergic and muscarinic receptors to cardiopulmonary dysfunction is lacking. Thus, we studied C57BL/6 mice 8 months after intraperitoneal injection of 100 trypomastigote f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Data (mean AE SD) are representative of three independent experiments (n ¼ 9 mice per group). associated with electrical conduction disturbances, diastolic dysfunction, lower O 2 consumption, and anaerobic threshold (26). We and others have shown that myocardial energetics and ATP content were compromised in infected rodents (38,42).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Data (mean AE SD) are representative of three independent experiments (n ¼ 9 mice per group). associated with electrical conduction disturbances, diastolic dysfunction, lower O 2 consumption, and anaerobic threshold (26). We and others have shown that myocardial energetics and ATP content were compromised in infected rodents (38,42).…”
Section: Discussionmentioning
confidence: 78%
“…Tissue damage and fibrosis associated with diffused inflammation become prominent during the chronic phase (13). Symptomatic defects include cardiomegaly, diffused myocarditis, self-perpetuating myofibril destruction, and a decline in LV ejection fraction (9,26,36), a picture reminiscent of the chronic form of Chagas disease observed in humans (24,25). Moderate-to-severe electrocardiographic and echocardiographic alterations evident in rodent hearts (3,7) are FIG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they could cause quantitative alterations in adrenergic and cholinergic receptors and, consequently, potential myocardial damage due to the cardiac autonomic dysfunctions known to occur in Chagasic cardiomyopathy (Hernandez et al, 2008;Ribeiro et al, 2009a;Rocha et al, 2006a;Rocha et al, 2006b). The clinical consequence of parasympathetic denervation is the absence of mechanisms, mediated by the vagus nerve, that trigger bradycardia or tachycardia in response to transient changes in blood pressure or venous return (Miziara et al, 2006;Ribeiro et al, 2009a;Rocha et al, 2009;Rocha et al, 2006b). However, the relative importance of the parasympathetic autonomic dysfunction has been recently questioned, raising the possibility that neurohormonal activation is the main underlying mechanism of disease progression (Davila et al, 2008).…”
Section: Cardiac Disautonomiamentioning
confidence: 99%
“…The result of either insult should promote the development of functional supersensitivity and/or up-regulation of postsynaptic mAChR in the cardiac muscle, due to a denervation phenomenon. Rocha et al (28) observed that C57BL/ 6 mice that have been inoculated intraperitoneally with T. cruzi trypomastigotes have an increased cardiac muscarinic receptor density 8 months after infection. In our in vivo chagasic rat model, the up-regulation of mAChR was restricted to the right ventricle from chronic chagasic adult rat heart, which suggests a selective denervation of the right ventricle vagal fibers.…”
Section: Discussionmentioning
confidence: 99%